Processing tomato response to arbuscular mycorrhizal fungi application under conventional production practice - Kristina Grozić; Igor Pasković; Tomislav Radić; Marina Lukić; Paula Žurga; Igor Palčić; Branimir Urlić; Mia Brkljača; Dean Ban; Joško Kaliterna; Jana Klanjac; Nikola Major; et al. (Journal of Central European Agriculture, 2021)
The potential effect of pre-inoculation of processing tomato (Solanum lycopersicum L.) plants with arbuscular mycorrhizal fungi (AMF) on yield and fruit properties was investigated in conventional production. Tomato seeds were sown in seedling trays filled with a substrate non-inoculated (AMF-) or inoculated (AMF+) by selected mycorrhizal strains. Seedlings were transplanted in Terra rossa soil and grown in conditions with mineral fertilization and irrigation. Tomato fruits were sampled at harvest. Tomato plants under both treatments had high levels of mycorrhizal colonization, due to applied inoculum (AMF+) or indigenous (AMF-) inoculum present in the soil. Applied AMF+ treatment increased P and decreased K content in tomato fruits. Content of trace elements such as As and V significantly increased, while Pb content significantly decreased in the fruits of AMF+ when compared to the AMF- treatment. No significant effect of AMF+ treatment was observed on yield, fruit quality (soluble solids, pH, total acidity, fruit firmness), lycopene and antioxidant activity of tomato fruits. The overall results suggest that processing tomato is highly susceptible to the indigenous AMF, while seedlings inoculation with selected AMF improves only total phenolic and P fruit content. This means that AMF have a potential application in commercial processing tomato production, however a targeted adaptation of management decissions is required for more extensive results.